Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1467-8535.2009.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Project management in instructional design: ADDIE is not enough

Abstract: In the digital age, instructional designers must possess both a sound instructional design knowledge base and solid project management skills that will enable them to complete courseware projects on time, on budget and in conformance with client expectations. Project management skills include the ability to apply repeatable processes, along with interpersonal skills such as communication and leadership skills. However, courses in project management are often absent from the higher education instructional desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In an analysis of team‐based instructional design processes, Hawkes and Coldeway () observed that the instructional designer's roles included project manager, coach of the faculty developer, reviewer and evaluator of the materials created by faculty, and media designer. Other studies showed that many instructional designers spend most of their time engaging in project management tasks which are essential to the successful development of curriculum (Van Rooij, ). For our team, the instructional designer had to be an expert in instructional design and also have project management skills in order to evaluate curriculum as well as manage the many processes involved in course and program development within established timelines.…”
Section: Curriculum Development Modelmentioning
confidence: 99%
“…In an analysis of team‐based instructional design processes, Hawkes and Coldeway () observed that the instructional designer's roles included project manager, coach of the faculty developer, reviewer and evaluator of the materials created by faculty, and media designer. Other studies showed that many instructional designers spend most of their time engaging in project management tasks which are essential to the successful development of curriculum (Van Rooij, ). For our team, the instructional designer had to be an expert in instructional design and also have project management skills in order to evaluate curriculum as well as manage the many processes involved in course and program development within established timelines.…”
Section: Curriculum Development Modelmentioning
confidence: 99%
“…Considering a project on the educational scenario that is currently being reframed, given the convergence of practices of different teaching modes, an instructional design that contemplates this diversity is needed, which extends to varied audience of students, demanding so that the activity of instructional design is able to perform similar pedagogies in different environments (Drira, Laroussi, Le Pallec, & Warin, 2012). Considering that the effective project management, according to Van Rooij (2010), requires knowing the characteristics of the actual project environment, instructional design projects must have its knowledge interconnected with educational practices of the teaching-learning process. For us, the difference between the models of project management and instructional design is the consequence of divergent perspectives between the management area and the educational area.…”
Section: Theoretical Assumptionsmentioning
confidence: 99%
“…However, JIT started crippling the development efforts due to the extensive time involved with designing each piece of the curriculum. The industry standard for curriculum developers that is increasingly found wanting due to its lack of practical application to real world situations is a methodology called ADDIE [5], and represents Analyze, Design, Develop, Implement, and Evaluate. It strongly correlates to the waterfall approach where the course must be understood at all levels in the beginning.…”
Section: A Impact Of Lean Approachesmentioning
confidence: 99%